Single-cell transcriptomics reveals immune dysregulation mediated by IL-17A in initiation of chronic lung injuries upon real-ambient particulate matter exposure - Rui Zhang; Shen Chen; Liping Chen; Lizhu Ye; Yue Jiang; Hui Peng; Zhanyu Guo; Miao Li; Xinhang Jiang; Ping Guo; Dianke Yu; Rong Zhang; et al. (Particle and Fibre Toxicology, 2022)
Abstract Background Long-term exposure to fine particulate matter (PM2.5) increases susceptibility to chronic respiratory diseases, including inflammation and interstitial fibrosis. However, the regulatory mechanisms by which the immune response mediates the initiation of pulmonary fibrosis has yet to be fully characterized. This study aimed to illustrate the interplay between different cell clusters and key pathways in triggering chronic lung injuries in mice following PM exposure. Results Six-week-old C57BL/6J male mice were exposed to PM or filtered air for 16 weeks in a real-ambient PM exposure system in Shijiazhuang, China. The transcriptional profiles of whole lung cells following sub-chronic PM exposure were characterized by analysis of single-cell transcriptomics. The IL-17A knockout (IL-17A−/−) mouse model was utilized to determine whether the IL-17 signaling pathway mediated immune dysregulation in PM-induced chronic lung injuries. After 16-week PM exposure, chronic lung injuries with excessive collagen deposition and increased fibroblasts, neutrophils, and monocytes were noted concurrent with a decreased number of major classes of immune cells. Single-cell analysis showed that activation of the IL-17 signaling pathway was involved in the progression of pulmonary fibrosis upon sub-chronic PM exposure. Depletion of IL-17A led to significant decline in chronic lung injuries, which was mainly triggered by reduced recruitment of myeloid-derived suppressor cells (MDSCs) and downregulation of TGF-β. Conclusion These novel findings demonstrate that immunosuppression via the IL-17A pathway plays a critical role in the initiation of chronic lung injuries upon sub-chronic PM exposure.